Assessment of Asthma Control and Severity among Children According to Global Initiative for Asthma Guidelines in Sulaimani City-Iraq - Hamawandi, Adnan M. H.; Ali, Kosar M; Naji, Ali Z. (European Scientific Journal, ESJ, 2016)
Background: Asthma is a common and potentially serious chronic disease that imposes a substantial burden on patients, their families and the community. Objective: Assessment of the level of asthma control and severity in asthmatic children in Sulaimani city according to the global initiative for asthma (GINA) guidelines. Methods: A cross-sectional study of 82 patients who are known cases of asthma, aged 5 – 15 years , from 1st of March 2014 to 1st of August 2014. Results: Out of 82 patients in our study, 20.8%were classified as having intermittent asthma all of them have well controlled asthma, 42.7% of those classified as having mild persistent asthma 65.7% of them have well controlled asthma, 26.8% of those classified as having moderate persistent asthma 54.5% of them have partly controlled asthma, and 9.8%of those classified as having severe persistent asthma the majority of them 87.5% have uncontrolled asthma and none of them reached to the controlled asthma level according to GINA guidelines. Regarding the peak expiratory flow (PFT) we notice that 58.8% of asthmatic children who were classified as having intermittent severity, their PEF measurements ranged between 160- 250 l/min while those with severe persistent asthma 75% of them have readings between 50-150 l/min. Conclusion: Current levels of asthma control in the Sulaimani city fall far short of the goals specified in the GINA guidelines for asthma management. Also there is a strong correlation between PEF measurements and the level of asthma severity,